Inseminação Artificial em Tempo Fixo (IATF) em Bovinos da Região de Jacundá-PA - Rodrigues, Ademir Pires (Universidade Federal do Tocantins, 2023)
This present study reports the activities developed during the required supervised training developed at the company Vagner Silva Ltda, located in the city of Jacundá – Pará, from 19 november 2015 to 1 february 2016, supervised by the Veterinarian Aldo Vagner da Silva Junior, completing a workload of 400 hours. During this period, I had the opportunity to follow and carry out activities in differents areas of activity of the veterinarian, such as Medicine and Animal Reproduction, contributing to my academic and professional future. The following study aims to emphasize the activities in the area of reproductive biotechnologies with emphasis on artificial insemination in fixed time, with a brief literature review.